Flood and riverbank erosion displaces of two different flood areas of Bangladesh: a situational study on their indigenous survival strategies - Karim, A.H.M Zehadul (Social Science Research Council, Govt. of Bangladesh, 2011)

(untitled)
This research on ‘Flood and Riverbank Erosion Displaces of Two Different Flood Areas of Bangladesh: A Situational Study on Their Indigenous Survival Strategies’ has been sponsored by Social Science Research Council of the Ministry of Planning, Government of Bangladesh. I acknowledge their assistance and cooperation in this regard. I express my sincere gratitude to Dr. Abdur Rahim Khan, Director of SSRC for his careful coordination of the program. This report would not have been completed if it was not followed up and chased by Dr.Abdur Rahim Khan with his own mechanisms; it is only because of his instigation and inspiration that I have been able to complete this project. It may be noted here that at the initial stage, the research was planned to include three villages as study locale and accordingly the data for that purpose were collected under the direct participation of the principal researcher. But due to some mishappenings, the whole lots of data were lost from the Vice Chancellor’s Office of Comilla University; and these were never found again. The matter was informed to the SSRC and being advised by them; I collected data again in 2010 and 2011 and shortened the horizon of this research by sqizzing it into two villages. The outcome of this research has been reported here in this monograph and it may be noted here that methodologically the theme of the research remained as it is, without having any modifications. At the field level, I was assisted with Md. Ruhullah, M. Asad and M. Ershad Hossain who completed their MSS degrees in Anthropology from Rajshahi University. All these three field-researchers along with a few more at the research areas were engaged in collecting data at the field level. I appreciate their seriousness in completing the work in a very meaningful ending. Being a full-time faculty member of International Islamic University Malaysia, I spent my time in coordinating the research while I went to Bangladesh on my periodical annual leave. I must express my gratitude to the university authority here in Malaysia to grant my leave which has been of a great use to my research.